The Amorite dynasty of Ugarit : historical implications of linguistic and archaeological parallels - Buck, Mary E., (Studies in the Archaeology and History of the Levant;, 2020)
"In The Amorite Dynasty of Ugarit Mary Buck takes a new approach to the field of Amorite studies by considering whether the site of Ugarit shares close parallels with other sites and cultures known from the Bronze Age Levant. When viewed in conjunction, the archaeological and linguistic material uncovered in this study serves to enhance our understanding of the historical complexity and diversity of the Middle Bronze Age period of international relations at the site of Ugarit. With a deft hand, Dr. Buck pursues a nuanced view of populations in the Bronze Age Levant, with the objective of understanding the ancient polity of Ugarit as a kin-based culture that shares close ties with the Amorite populations of the Levant. .